Recycling of Copper and Gold from Waste Printed Circuit Boards by Leaching Followed by Solvent Extraction - Singh K.K.; Rao M.D. (My University, 2025)
This article presents a two-stage, eco-friendly hydrometallurgical route for the recovery of gold from the delaminated metallic layers of waste mobile phone Printed Circuit Boards (PCBs). The downsized PCBs were treated with an organic solvent dimethylacetamide (DMA) for the separation of metallic fraction from non-metallic glass fibre. The liberated metallic sheets are used for the selective dissolution of copper in an aqueous leaching reagent. Influence of various parameters such as type of leaching reagent, the concentration of the solution, temperature, time, and pulp density is optimized for the effective leaching (almost 100%) of copper. Results show that 3 M nitric acid is a suitable reagent for copper leaching but gold remained in solid residue. In the second stage, the separated residue is used for the recovery of gold by sulphuric acid with a combination of halide salt. Results have shown that almost 92% of gold is recovered at the optimized parameters. Solvent extraction with 0.1M tertiary amide reveled the selective and quantitative recovery of gold from gold leach solution. © 2023, The Minerals, Metals & Materials Society.